PENGARUH SPONSORSHIP, EVENT LOKAL, KEGIATAN EDUKASI DAN PENAWARAN TERHADAP PENINGKATAN PENJUALAN SARI ROTI DI KOTA BENGKULU - Hamdani, Hamdani; Sismanto, Adi (UM. Bengkulu, 2026)
This study aims to determine the influence of sponsorship, local events, educational activities, and offers on the increase in Sari Roti sales in Bengkulu City, both partially and simultaneously. Several factors will be discussed in this study, including sponsorship, local events, educational activities, and offers related to the increase in Sari Roti sales in Bengkulu City, with 170 respondents. In this research, the author uses data collection methods through observation, interviews, and questionnaires. Several data analysis techniques are used in this study, including instrument tests such as validity test, reliability test, classical assumption test, coefficient of determination, and hypothesis testing. From the results of the multiple linear regression test, the regression equation obtained is as follows: Y = 0.105 + 0.016 (X1) + 0.085 (X2) + 0.447 (X3) + 0.454 (X4) + 0.174. Meanwhile, the hypothesis testing results show that the Sponsorship variable (X1) has a t-value of 1.676 (higher than the t-table value, or t-value > 1.654, as seen in the t-distribution table), with a significance level of 0.096 (significant > 0.05). The Local Event variable (X2) has a t-value of 2.660 (higher than the t-table value, or t-value > 1.654, as seen in the t-distribution table), with a significance level of 0.009 (significant < 0.05), and the Educational Activities variable (X3) has a t-value of 11.481 (higher than the t-table value, or t-value > 1.654, as seen in the t-distribution table), with a significance level of 0.0009 (significant < 0.05). The Offer variable (X4) has a t-value of 9.879 (higher than the t-table value, or t-value > 1.654, as seen in the t-distribution table), with a significance level of 0.000 (significant < 0.05). The F-test results show that (F-value > F-table), which is (17.778 > 2.42), and the significance level (sig < α = 0.000 < 0.05), so it can be concluded that H4 is accepted. This means that, simultaneously, the variables Sponsorship (X1), Local Events (X2), Educational Activities (X3), and Offers (X4) significantly influence the increase in Sari Roti sales (Y) in Bengkulu City. Keywords: Sponsorship, Local Events, Educational Activities, Offers, Sales Increase..